Підсумки інтродукції видів Tilia L. в умовах Києва - Doroshenko, O.K. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2005)
Seventin species and three forms of Tilia L. were introduced in arboretum of NBG of the NAS of Uk raine. As a result five species, to wit T. platyphyllos Scop., T. europaea L., T. begoniifolia Stev., T. dasystyla Stev. аnd T. neglecta Spach. were recommended for use. It was cited the species for study and testing and some species, which must be limited for use.